Photoorganocatalytic synthesis, characterization, crystal structure of two schiff bases and their In Vitro and In Silico evaluations as cholinesterase inhibitors - Abbasova, Gulu; Medjidov, Ajdar; Ismayilov, Rayyat; Tagiyev, Dilgam; Sertcelik, Mustafa; Hokelek, Tuncer; Huseynova, Mansura (Elsevier, 2025)
Given that substances containing an imine or azomethine fragment are included in the group of physiologically active substances, the synthesis of new Schiff bases or the development of new synthesis methods for existing ones is of interest. Two Schiff bases were synthesized by the photoorganocatalytic method and characterized by elemental analysis, UV-Vis, IR spectroscopy and X-ray single-crystal analysis. The reactions were carried out under light irradiation (household lamps 2 x 15 W) with stirring at room temperature without heating, resulting in yields of 83 and 80 %, respectively for I and II. To obtain the target product, aromatic aldehydes 5-bromosalicylic aldehyde and ortho-vanillin, as well as 2-amino-5-methylpyridine, derivatives of pyridine, representatives of heterocyclic amines, were used. Compounds were prepared by the aldol condensation. Cognitive impairment, known as dementia is typically associated with disorders of the central nervous system, particularly Alzheimer's disease. The few drugs that are currently on the market are not enough to help patients with this illness live a better life. As a result, new compounds (I and II) were synthesized and produced as inhibitors of human butyrylcholinesterase (hBChE) and human acetylcholinesterase (hAChE). The compounds I and II showed dual inhibitory efficiency against hAChE with IC50 values of 25.47 and 18.90 mu M, respectively. On the other hand, the compounds showed dual inhibitory efficiency against hBChE with IC50 values of 33.68 and 30.51 mu M, respectively, according to the in vitro evaluation. Their KI constants were even lower than those of tacrine, a common medication (Kis of 38.92 +/- 5.66 mu M for hAChE and 68.52 +/- 8.40 nM for hBChE). Additionally, molecular docking and molecular dynamic studied for both enzymes and both complexes. The compounds targeting hAChE and hBChE may offer potential benefits in the treatment of neurodegenerative diseases. By influencing cholinergic signaling, these compounds could aid in symptom management. The comprehensive analysis of the 100 ns MD simulations for both I and II with hAChE and hBChE underscores the critical role of ligand-protein interactions in drug development.
Keywords: Aromatic Aldehydes; Photoorganocatalytic Synthesis; Crystal Structure; Hirshfeld Surface Analysis; Enzyme Inhibition; In Silico